Comparison of multi echo T(2) relaxation and steady state approaches for myelin imaging in the central nervous system - Dvorak, Adam V. (Sci Rep, 2021)
The traditional approach for measuring myelin-associated water with quantitative magnetic resonance imaging (MRI) uses multi-echo T(2) relaxation data to calculate the myelin water fraction (MWF). A fundamentally different approach, abbreviated “mcDESPOT”, uses a more efficient steady-state acquisition to generate an equivalent metric (f(M)). Although previous studies have demonstrated inherent instability and bias in the complex mcDESPOT analysis procedure, f(M) has often been used as a surrogate for MWF. We produced and compared multivariate atlases of MWF and f(M) in healthy human brain and cervical spinal cord (available online) and compared their ability to detect multiple sclerosis pathology. A significant bias was found in all regions (p < 10(–5)), albeit reversed for spinal cord (f(M)-MWF =  − 3.4%) compared to brain (+ 6.2%). MWF and f(M) followed an approximately linear relationship for regions with MWF <  ~ 10%. For MWF >  ~ 10%, the relationship broke down and f(M) no longer increased in tandem with MWF. For multiple sclerosis patients, MWF and f(M) Z score maps showed overlapping areas of low Z score and similar trends between patients and brain regions, although those of f(M) generally had greater spatial extent and magnitude of severity. These results will guide future choice of myelin-sensitive quantitative MRI and improve interpretation of studies using either myelin imaging approach.